FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA PEMANEN SAWIT PT. DESARIA PLANTATION MINING DI KECAMATAN KINAL KABUPATEN KAUR - Dipry Sipriani; Basuki Sigit Priyono; Agus Purwoko (Universitas Teuku Umar, 2017)
Labor productivity is very important to the production process with supporting the human resources factors, because the production activities are influenced by the ability of labor. Productivity serves as a measure of development in developingperformance quality. The objectives of this research are: (1) Calculating productivity level of harvesting workers and (2) Identifying factors affecting labor productivity of palm oil harvesters in PT. Desaria Plantation Mining (PT.DPM). This research was conducted in April-May 2017. The location of this research is done by purposivelly. The respondent collecting in this research was done by census method, where the respondents were 34 respondents, and the data were analyzed using multiple linear regression analysis. The result of the research shows that the productivity of the palm oil harvesting worker is high because they exceeds from the standard that is 839,76 janjang/month. The other hand the result of estimation of t test show that age factor and working experiency of palm oil harvest the have real influence to the productivity of palm harvester at PT. Desaria Plantation Mining (PT.DPM).